THE TECHNIQUES IN TEACHING LISTENING SKILL - Nor, Hidayah (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2014)
Listening is very important skill in language because by listening students can produce language like speaking and writing by vocabulary that they get from listening. The English teacher of MAN 3 Banjarmasin used some techniques in teaching listening using the facilities in language laboratory such as tape cassette, television, and VCD/DVD. This research described the techniques in teaching listening skill of the Islamic high school students. The subjects of this study were an English teacher and 48 students of the tenth grade at MAN 3 Banjarmasin in Academic Year 2009/2010. To collect the data, it was used some techniques such as observation, interview, and documentary. Then all data were analyzed using descriptive method qualitatively and quantitatively, by concluding inductively. The result indicates that the techniques in teaching listening applied by the English teacher of the tenth grade students at MAN 3 Banjarmasin in Academic Year 2009/2010 are: Information Transfer, Paraphrasing and Translating, Answering Questions, Summarizing, Filling in Blanks, and Answering to Show Comprehension of Messages. The studentsâ ability of listening comprehension using six techniques is categorized in very high, high, and average levels.Keywords: listening techniques, teaching listening skill